2022
DOI: 10.1007/s00404-022-06473-9
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid argon plasma coagulation (HybridAPC) versus sharp excision for the treatment of endometriosis: a prospective randomized clinical trial

Abstract: Purpose Endometriosis is a benign, but potentially serious gynaecological condition in terms of abdominal pain and impaired fertility. Laparoscopic excision techniques are considered the therapeutic standard. HybridAPC is presented as a novel technique for the non-contact thermal ablation of peritoneal endometriosis with simultaneous protection of the underlying thermosensitive structures by creating a needle-free elevated fluid cushion which enables a safer exposure and distance, as well as pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(34 reference statements)
0
0
0
3
Order By: Relevance
“…O tratamento da endometriose, inicialmente, deve ter como objetivo o alívio dos sintomas, em especial da dor, além da melhora da fertilidade sempre que possível (BECKER et al, 2024;KECKSTEIN et al, 2023;LI et al, 2022). No entanto, para além dos tratamentos já existentes e aprovados para endometriose, como o manejo hormonal com intenção de reduzir níveis de estradiol e, na falha ou impossibilidade deste, a utilização de cirurgias, novas formas de tratamento são necessárias dado que mesmo após ressecções cirúrgicas bem sucedidas do tecido endometrial ectópico, sintomas podem persistir ou recorrer (BECKER et al, 2024;LI et al, 2022).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…O tratamento da endometriose, inicialmente, deve ter como objetivo o alívio dos sintomas, em especial da dor, além da melhora da fertilidade sempre que possível (BECKER et al, 2024;KECKSTEIN et al, 2023;LI et al, 2022). No entanto, para além dos tratamentos já existentes e aprovados para endometriose, como o manejo hormonal com intenção de reduzir níveis de estradiol e, na falha ou impossibilidade deste, a utilização de cirurgias, novas formas de tratamento são necessárias dado que mesmo após ressecções cirúrgicas bem sucedidas do tecido endometrial ectópico, sintomas podem persistir ou recorrer (BECKER et al, 2024;LI et al, 2022).…”
Section: Discussionunclassified
“…Contudo, a formação de aderências foi encontrada em apenas 5% das lesões tratadas com HybridAPC em comparação com o grupo que recebeu excisão acentuada (10%), não sendo registradas complicações intra e pós-operatórias em ambos os grupos. Assim, os autores atribuem à HybridAPC a viabilidade de um novo tratamento cirúrgico promissor com impacto na prevenção de aderências, além de ser um método seguro, rápido e que permite a preservação de tecidos, fator determinante no tratamento da endometriose peritoneal (KECKSTEIN et al, 2023).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…It is unknown whether the results of studies conducted on patients without endometriosis could be generalised on patients with endometriosis. Keckstein et al ( 2023 ) recently gave an example on the importance of the surgical technique in preventing adhesion formation. They demonstrated that the use of hybrid argon plasma coagulation reduces the risk of adhesiogenesis compared to sharp excision of endometriosis.…”
Section: Discussionmentioning
confidence: 99%